IK is essentially involved in ciliogenesis as an upstream regulator of oral-facial-digital syndrome ciliopathy gene, ofd1 - Hye In Ka; Mina Cho; Seung-Hae Kwon; Se Hwan Mun; Sora Han; Min Jung Kim; Young Yang (Cell & Bioscience, 2023)
Abstract Background The cilia are microtubule-based organelles that protrude from the cell surface. Abnormalities in cilia result in various ciliopathies, including polycystic kidney disease (PKD), Bardet-Biedl syndrome (BBS), and oral-facial-digital syndrome type I (OFD1), which show genetic defects associated with cilia formation. Although an increasing number of human diseases is attributed to ciliary defects, the functions or regulatory mechanisms of several ciliopathy genes remain unclear. Because multi ciliated cells (MCCs) are especially deep in vivo, studying ciliogenesis is challenging. Here, we demonstrate that ik is essential for ciliogenesis in vivo. Results In the absence of ik, zebrafish embryos showed various ciliopathy phenotypes, such as body curvature, abnormal otoliths, and cyst formation in the kidney. RNA sequencing analysis revealed that ik positively regulated ofd1 expression required for cilium assembly. In fact, depletion of ik resulted in the downregulation of ofd1 expression with ciliary defects, and these ciliary defects in ik mutants were rescued by restoring ofd1 expression. Interestingly, ik affected ciliogenesis particularly in the proximal tubule but not in the distal tubule in the kidney. Conclusions This study demonstrates the role of ik in ciliogenesis in vivo for the first time. Loss of ik in zebrafish embryos displays various ciliopathy phenotypes with abnormal ciliary morphology in ciliary tissues. Our findings on the ik–ofd1 axis provide new insights into the biological function of ik in clinical ciliopathy studies in humans.